Педагогическая эвристика в структуре личностно ориентированного образования - Велишаева, А.Э. (Культура народов Причерноморья, 2006)
Цель статьи: провести анализ различных трактовок педагогической эвристики, определить ее задачи, основные структурные элементы и уровни в системе личностно ориентированного образования. This article is devoted to the pedagogical heurist in the personal oriented education that is the analyses of different approaches to the interpretation of pedagogical heurist is done, the tasks, methods and the main structural elements are determined. The peculiarities of theoretical, methodological, individual-practical levels of pedagogical heurist are examined. The functions of personality are determined on every level, principles of government with heuristic activity are revealed. Important conclusions are done.